Personality factors and pandemic-related behaviors - Williamson, Jessica (Frontiers in Psychology, 2024)
The purpose of the current study was to determine whether there are personality differences (the HEXACO model, narcissism, sadism, compassion for others) in mask-wearing, social distancing, and hoarding. Findings: Those who always wore masks were significantly higher in compassion for others and significantly lower in sadism compared to those who did not always wear masks. Those who always socially distanced (compared to those who did not) were significantly higher in openness, compassion for others, and conscientiousness. Those who hoarded were significantly lower in agreeableness than those who did not hoard. Conclusions: Perhaps physicians may use information to boost states of altruistic-type traits (agreeableness, compassion for others) while educating patients during visits in order to increase the likelihood of receiving vaccinations or booster shots.